PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM E-MARKETPLACE PADA PENGRAJIN GERABAH DESA BUMI JAYA SERANG BANTEN - Siti Nurul Hamidah; Uzieka Arsiya Rosadha; Abdul Hafidz Sufiyana; Ari Alfiansyah; Mutamimatussifah Mutamimatussifah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
Pottery is a traditional product that is still being made and developed. But the existence of pottery today has begun to diminish its interest because it has to compete with modern products. Therefore, the need for empowerment of Small and Medium Industries, especially the pottery industry to be able to compete in the modern market. This paper aims to: (1) know the potential of proper local empowerment in Kampung Gerabah Bumi Jaya Serang Banten, (2) identify the right model of economic development and empowerment, (3) Analyze the usefulness and benefits of technology in the economy of the pottery industry through E-Martketplace on pottery craftsmen in Kampung Gerabah Desa Bumi Jaya Serang Banten. The method used is a descriptive qualitative approach to obtain relevant data in community empowerment, especially empowerment in pottery craftsmen in Kampung Gerabah Bumi Jaya Serang Banten. The results showed that empowerment through e-Marketplace can be done on pottery craftsmen in Bumi Jaya Village. Pottery sales through e-marketplaces have a high opportunity if developed well and continuously and there are innovations in pottery products.